Lipoprotein receptors in cultured bovine endothelial cells - Strumpfer, A E M (Division of Medical Biochemistry and Structural Biology, 2018)
Endothelial cells take up and degrade both low density lipoproteins and low density lipoproteins which have been modified by acetylation (AcLDL). In this study, receptors that may be involved in the uptake of these lipoproteins were characterized. The cells used were aortic endothelial cells obtained from a bovine foetus, with subsequent cloning (A₃Cl₂). A cell culture system which closely resembled the in vivo monolayer was established, by growing the cells on gelatin-coated Petri dishes. Endothelial cell and lipoprotein interactions were examined by incubating the cells with ¹²⁵I-labelled lipoproteins under various conditions. The main findings were the following: The receptor affinity of bovine aortic endothelial cells was higher for AcLDL than that for LDL. The half-maximal rates of degradation, obtained from degradation saturation curves which were linearized using the Scatchard method, were about 20 μg protein/ml for LDL and about 2 μg protein/ml for AcLDL. Analyses of binding data were not accurate due to the large amount of non-saturable material bound. However, the bulk of the lipoproteins was taken up and degraded via the saturable process. Competition studies demonstrated that there were two distinct receptors for LDL and AcLDL on the endothelial cells. AcLDL did not compete with LDL for the LDL receptor, and conversely LDL did not compete with AcLDL for the AcLDL receptor. The receptor activities for LDL and AcLDL were examined as a function of culture age. Sparse cultures incubated at low lipoprotein concentrations (10-20 μg protein/ml) had a higher receptor activity for LDL than for AcLDL. In contrast, confluent cultures, catabolized more AcLDL than LDL. In comparing sparse to confluent cell cultures, the rate of ¹²⁵1- labelled LDL degradation decreased about twice, while the degradation rates of ¹²⁵I-labelled AcLDL increased about three times. Whereas the LDL receptor could be regulated, the AcLDL receptor was not as susceptible to regulation. Up-regulation was measured by pre-incubation of the cells with lipoprotein-deficient serum medium (LPDS-medium) for 48 h. Using degradation data, the LDL receptor was up-regulated about 4-fold, whereas the AcLDL receptor was not up-regulated under these circumstances. Down-regulation by incubating the cells with 25-hydroxycholesterol for 24 h resulted in a 96 % decrease in the LDL receptor activity and only a 30 % decrease in the AcLDL receptor activity. Furthermore, both LDL and AcLDL could down-regulate the LDL receptor, but neither could down-regulate the AcLDL receptor. Upon exposing endothelial cells for 72 h to either LDL or AcLDL, it was found that the total amount of cellular cholesterol increased (by about 50 %). However, the increase of total cholesterol was largely in the form of free cholesterol. This is in contrast to macrophages, where the increase in total cholesterol upon exposure to AcLDL is largely in the form of cholesteryl esters.